Fractional attitude-reactive control for robust quadrotor position stabilization without resolving underactuation. (August 2016) - Izaguirre-Espinosa, C.; Muñoz-Vázquez, A.J.; Sánchez-Orta, A.; Parra-Vega, V.; Sanahuja, G.
Abstract: Quadrotors are Unmanned Aerial Systems (UAS), whose nonlinearities, uncertainties, and unavoidable aerodynamic disturbances stand for a difficult control problem. Additionally, the highly nonlinear coupling between the position and the orientation dynamics exacerbates the underactuation problem when the objective is the position tracking. In this paper, aiming at designing a robust position controller without resolving underactuation, a novel " reactive orientation control " is proposed. The orientation controller is model-free and it is build upon differintegral fractional operators to react to a continuous and bounded additive term that stands for an affine exogenous position controller. Such term indeed becomes an attitude disturbance that is purposely injected to displace the quadrotor towards the desired position of the underactuated coordinates. The closed-loop analysis shows that the norm of the transfer function between the disturbance and the position tracking error is minimized for a stable and robust position regime. Simulations and experimental results are given to discuss the feasibility of the proposed scheme. Abstract : Highlights: Robust stabilization without resolving underactuation. The fractional attitude reactive controller assures boundedness of the orientation coordinates. Input–output stability is demonstrated against square integrable disturbances. Fractional operators filter out high frequencies from the control signal. Experiments and simulations show the reliability of the proposed scheme.